PENGUKURAN CUSTOMER RETENTION PENGGUNA TELKOMSEL SAMARINDA: ADOPSI RELATIONSHIP QUALITY THEORY - Alya Andaniy; Wira Bharata (Value : Jurnal Manajemen dan Akuntansi, 2023)
The Indonesian population is classified as a society that is dependent on the internet. With an internet connection, it is easier for people to communicate over long distances, find information easier, make it easier to access various services and entertainment, and much more. Telkomsel is currently the cellular operator with the most users in Indonesia. Many previous studies have discussed the factors that encourage consumers to use Telkomsel. The purpose of this study is to determine the effect of service quality, customer satisfaction, and customer trust on customer retention. This study adopts Relationship Quality Theory which is the first model for measuring customer retention. This research method uses a quantitative approach. The population in this study are Telkomsel users in Samarinda City. In this study using nonprobability sampling as a sampling technique with a total sample of 100 respondents. Empirical data proves that all the hypotheses that have been put forward in this study are acceptable. The relationship of each variable tested is positive and significant. The findings of this study show that service quality, customer satisfaction, and customer trust are important aspects that have an impact on customer retention. Keywords: Customer Retention, Relationship Quality, Telkomsel